2017
DOI: 10.1074/jbc.m117.790568
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid preserves visual function by maintaining correct disc morphology in retinal photoreceptor cells

Abstract: Docosahexaenoic acid (DHA) has essential roles in photoreceptor cells in the retina and is therefore crucial to healthy vision. Although the influence of dietary DHA on visual acuity is well known and the retina has an abundance of DHA-containing phospholipids (PL-DHA), the mechanisms associated with DHA's effects on visual function are unknown. We previously identified lysophosphatidic acid acyltransferase 3 (LPAAT3) as a PL-DHA biosynthetic enzyme. Here, using comprehensive phospholipid analyses and imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 56 publications
6
112
0
Order By: Relevance
“…In addition, a recent study comparing in vitro LPLAT activities and tissue PC compositions also suggested that levels of DHA‐containing GPLs may be primarily regulated by LPAAT activities functioning in the Kennedy pathway rather than other LPLATs functioning in the Lands’ cycle . Recently, we also reported that in LPAAT3 KO mice DHA‐containing GPLs were greatly decreased , consistent with the idea that DHA‐containing GPLs are primarily produced through the Kennedy pathway.…”
Section: Production Of ω‐3 Pufa‐containing Gplssupporting
confidence: 84%
See 4 more Smart Citations
“…In addition, a recent study comparing in vitro LPLAT activities and tissue PC compositions also suggested that levels of DHA‐containing GPLs may be primarily regulated by LPAAT activities functioning in the Kennedy pathway rather than other LPLATs functioning in the Lands’ cycle . Recently, we also reported that in LPAAT3 KO mice DHA‐containing GPLs were greatly decreased , consistent with the idea that DHA‐containing GPLs are primarily produced through the Kennedy pathway.…”
Section: Production Of ω‐3 Pufa‐containing Gplssupporting
confidence: 84%
“…Mislocalization of rhodopsin in the perinuclear region was seen in both Mfsd2a and LPAAT3 KO mice (Fig. A) . As DHA‐containing GPLs may also promote membrane fusion and fission, another possible function for DHA‐containing GPLs in photoreceptor cells might be to promote trafficking of rhodopsin from endoplasmic reticulum to the plasma membrane via the Golgi apparatus (Fig.…”
Section: Roles Of Dha‐containing Gpls In Various Tissuesmentioning
confidence: 91%
See 3 more Smart Citations